Designing an Android application using the software platform (FLUTTER) to alert the times of medical treatments (MT) - Mohammed, Layla Esam; Mohammed, Shatha Abdullah (Eximia, 2022)
This research dealt with the use of the descriptive analytical method for how to analyze, design and develop an application (therapeutic dates) By studying the engineering steps and stages for developing a remedial appointment application, where the SDLC model was used to clarify the stages of application design, starting from the planning stage of how to build the application and what its specifications are and ending with publishing the application on the platforms of google play and the app store to benefit from it in Reminder of medication appointments The star UML language was also used to design and analyze our application, to document how to access it, add the name and type of treatment to alert the times it was taken, as well as the user's interaction with the application through its use of the application, where the Unified Modeling Language (UML) can help to model systems in different ways, and this language is designed to be simple and easy to use, and the use case diagram, activity diagram, and flow chart diagram models were used. To clarify the stages of software engineering for the design of the application and how it interacts with the user, and after the completion of the application design, an analytical study was conducted for the application’s work from the users’ point of view, and an electronic questionnaire was made that consisted of the following samples (students pharmacists and students of medical and health specialties, pharmacists, doctors, Patients, other groups) where the application was tested by them, their opinions were collected, and the results of this questionnaire were analyzed using screening processes for the results of the questions, and positive and encouraging results were obtained.